Discovery of TaFeSb-based half-Heuslers with high thermoelectric performance - Hangtian Zhu (Nature Portfolio, 2019)
The discovery of thermodynamically stable thermoelectric materials for power generation has relied on empirical methods that were not effective. Here, the authors apply the inverse design approach to identify and experimentally realize TaFeSb-based half Heuslers with high thermoelectric performance.